PENGEMBANGAN MEDIA ALAT BANTU RENANG GALON RAKIT UNTUK PEMBELAJARAN RENANG PEMULA - Galuh Hendi; Catur Wahyu Priyanto (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
Research and development (R&D) is carried out by identifying potentials and problems, gathering information, designing products, making products, validating experts, and testing products. The development of swimming aids was validated by material experts and media experts and 10 respondents. The subjects of this research are students PJKR Unwahas who meet the requirements to serve as respondents. The data collection technique used was a questionnaire instrument. The data analysis technique of this research is descriptive qualitative and percentage quantitative descriptive. The results showed that the gallon raft aids was feasible to use as a learning aid for swimming. These results are obtained from the latest validation results of a) material expert at 85% or feasible; b) media expert 80.8% or feasible; c) Respondents of 85,4% or feasible. Thus, the conclusion is that the gallon raft aids are declared feasible for swimming learning